Nurses' knowledge of heart failure in a North Carolina community hospital - Swiger, Natalie Rhiannon (2015)
Heart failure (HF) is an epidemic affecting approximately 5.1 million people in the United States and is one of the most expensive cardiovascular illnesses, costing the nation an estimated $32 billion each year (CDC, 2013). There is no cure for HF, but following guidelines established by the American Heart Association can contribute to decreased mortality, improved quality of life, and decreased hospital admissions. Nurses play an essential role in providing comprehensive HF self-management education to patients, and thus, should be knowledgeable about HF principles themselves. Research suggests that nurses may not have adequate knowledge of HF management to educate patients, and consequently, are not optimally prepared to provide HF education (Hart, Spiva, & Kimble, 2011).This was an exploratory, descriptive study with a survey design seeking to describe nurses’ knowledge of HF self-management principles within a community hospital in North Carolina. The Nurses’ Knowledge of Heart Failure Education Principle questionnaire developed by Dr. Nancy Albert (2002) was utilized to determine which HF education topics nurses were knowledgeable about and which topics they were deficient. Thirty-two registered nurses agreed to participate, with a mean knowledge score of 15.75 (78.75% correct). Consistent with previous studies, nurses scored lowest on knowledge related to transient dizziness (28.1% correct), asymptomatic hypotension (18.8% correct), daily weight assessment (25% correct), and salt substitutes (53.1% correct). Findings confirm previous work suggesting that nurses may not be adequately prepared to educate patients with HF about self-management.This aspect of nursing education is important, because nurses caring for HF patients need to have sufficient knowledge of HF self-management principles in order to provide optimal education to patients. Lack of adequate education for HF patients results in noncompliance with outpatient treatment modalities and ultimately leads to hospital readmissions related to HF exacerbation. Nurses with adequate knowledge of HF can provide better education to patients on how to manage their HF, potentially reducing hospital readmission rates related to HF and improving patients’ overall quality of health.